Selected terms with a participial component in the language of education. A morphological and semantic analysis - Makarewicz, Renata (Papers in Linguistics, 2019)
This paper concerns educational linguistics and presents a morphological and semantic analysis of the terms used in the language of education that contain a participial component. These terms appear in legal documents and materials used for teachers’ professional development. Some of the analysed cases raise doubts about their appropriateness and semantic clarity. This paper aims to explain these doubts and decide on the correctness of each case. The participles used in the studied terms are subjected to a morphological analysis. The motivation behind the formation of the terms is described. The participles are analysed according to the categories of tense and voice. The paper analyses active and passive participles, referencing approaches, present in subject literature, to the trend of the adjectivisation of adjectival participles. Describing word-formation mechanisms involves rules of semantic cohesion, which underlie the pronunciations of correctness in terms of the appropriateness of use. The observed semantic innovations are presented in the context of educational models (the humanistic model of the school). The Polish term ucząca się szkoła is inspired by the English term learning school and is an example of neosemantisation. In addition to presenting a linguistic analysis of the passive participles, including dictionary references, this paper also presents these participles in light of the educational changes that have been observed for the last thirty years. The analysis has yielded the conditions of appropriateness and clarity for the terms containing active and passive adjectival participles that appear in the language of education. These terms are used to shorten utterances. However, sometimes specialised language is required.